2018
DOI: 10.1002/mds.27437
|View full text |Cite
|
Sign up to set email alerts
|

Neurorehabilitation therapy in spinocerebellar ataxia type 2: A 24‐week, rater‐blinded, randomized, controlled trial

Abstract: A comprehensive 24-week rehabilitation program significantly improves the motor cerebellar symptoms of spinocerebellar ataxia type 2 patients as assessed by the ataxia rating score likely as result of the partial preservation of motor learning and neural plasticity mechanisms. These findings provide evidence in support of this therapeutic approach as palliative treatment in spinocerebellar ataxia type 2 suggesting its use in combination with other symptomatic or neuroprotective drugs and in prodromal stages. ©… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 41 publications
4
35
0
1
Order By: Relevance
“…At present, there is no disease-modifying therapy for SCAs, only the symptomatic treatment and the methods of a palliative care are used to support SCA patients [120]. A recent 24-week, rater-blinded, randomized, controlled trial on SCA2 patients revealed that the tested rehabilitation program significantly improved the SARA scores of SCA2 patients likely as a result of the partial preservation of the motor learning and neural plasticity mechanisms suggesting that palliative treatment does have an actual effect in the treatment of SCA2 patients [121]. Current clinical studies show that some ataxia signs can be partly improved pharmacologically by treatment with 4-aminopyridine, riluzole, valproic acid, and thyrotropinreleasing hormone, whereas lithium and deferiprone have a negative effect or its absence [122].…”
Section: Ataxiamentioning
confidence: 99%
“…At present, there is no disease-modifying therapy for SCAs, only the symptomatic treatment and the methods of a palliative care are used to support SCA patients [120]. A recent 24-week, rater-blinded, randomized, controlled trial on SCA2 patients revealed that the tested rehabilitation program significantly improved the SARA scores of SCA2 patients likely as a result of the partial preservation of the motor learning and neural plasticity mechanisms suggesting that palliative treatment does have an actual effect in the treatment of SCA2 patients [121]. Current clinical studies show that some ataxia signs can be partly improved pharmacologically by treatment with 4-aminopyridine, riluzole, valproic acid, and thyrotropinreleasing hormone, whereas lithium and deferiprone have a negative effect or its absence [122].…”
Section: Ataxiamentioning
confidence: 99%
“…Studies have shown that rehabilitation training may improve the balance function of SCA patients [14][15][16] , but there is no consistent recommendation for rehabilitation training. It is therefore necessary to evaluate postural stability to optimise rehabilitation programmes for SCA3 patients to improve their function, reduce the risk of falling and improve their quality of life.…”
mentioning
confidence: 99%
“…Cuba is the country with the world's highest prevalence of SCA2 (28 mutation carriers per 10 inhabitants), particularly in the province of Holguín, where it reaches around 182 mutation carriers per 10 inhabitants as a result of a founder effect …”
mentioning
confidence: 99%
“…To date, therapies for SCA2 are largely symptomatic, controlling symptoms rather than mitigating disease progression . However, neurorehabilitation approaches have shown significant benefits for motor and nonmotor features of the disease …”
mentioning
confidence: 99%
See 1 more Smart Citation